The Antifungal Properties of Epidermal Fatty Acid Esters: Insights from White-Nose Syndrome (WNS) in Bats - Craig L. Frank; Katherine G. Sitler-Elbel; Anna J. Hudson; Melissa R. Ingala (Molecules, 2018)
Numerous free fatty acids (FFAs) are known to have potent antifungal effects. The mammalian epidermis contains both FFAs and multiple classes of fatty acid esters, including 1-monoacylglycerols and wax esters. We thus hypothesized that wax esters and 1-monoacylglycerols composed of antifungal fatty acids would also have antifungal properties. We tested this hypothesis by examining the effects of 1-monoacylglycerols, 1,3-diacylglycerols, and wax esters on the growth of Pseudogymnoascus destructans (Pd), the fungus that causes White-nose Syndrome (WNS) in North American bats by invading their epidermis. Laboratory experiments with Pd cultures demonstrated that: (a) three 1-monoacylglycerols (1-monopalmitolein, 1-monoolein, and 1-monolinolein), as well as, (b) two wax esters, behenyl oleate and behenyl palmitoleate, profoundly inhibit Pd growth. The normal growth cycle of Pd was interrupted by addition of two cholesterol esters to the media as well. A bat species resistant to cutaneous Pd infections has these 1-monoacylglycerols in the epidermis, and another Pd resistant bat species has these wax esters in the sebum, thus cutaneous lipid composition is one factor which enables some bats to avoid WNS. Our experiments also revealed that the fatty acid esters which inhibit Pd growth are not hydrolyzed by the lipases secreted by this fungus, whereas the esters that do not inhibit Pd growth are hydrolyzed.